1991
DOI: 10.1016/s0006-3495(91)82176-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid interaction of Pseudomonas aeruginosa exotoxin A. Acid-triggered permeabilization and aggregation of lipid vesicles

Abstract: We have investigated the interaction of Pseudomonas exotoxin A with small unilamellar vesicles comprised of different phospholipids as a function of pH, toxin, and lipid concentration. We have found that this toxin induces vesicle permeabilization, as measured by the release of a fluorescent dye. Permeabilization is due to the formation of ion-conductive channels which we have directly observed in planar lipid bilayers. The toxin also produces vesicle aggregation, as indicated by an increase of the turbidity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
4
22
0
Order By: Relevance
“…Instead, although oligomers were shown to cause a much greater release of calcein than trypsin-activated toxin monomers, both forms of the toxin appeared to act instantaneously, at least within the time resolution of the instrument, upon addition of the toxin to the vesicle suspension Rausell et al, 2004a). This result is very surprising considering that although calcein release can be very rapid, it is nevertheless expected to take place at a measurable rate (Schwarz and Robert, 1990) as was reported for the Escherichia coli colicin E1 (Kayalar and Düzgüneçs, 1986) and hemolysin (Menestrina, 1988), the Clostridium tetani tetanus toxin (Menestrina et al, 1989), the Pseudomonas aeruginosa exotoxin A (Menestrina et al, 1991) and the mosquitocidal binary toxin from Bacillus sphaericus , to mention only a few examples of calcein-efflux experiments conducted with bacterial pore-forming toxins. Clearly, pore formation by Bt toxins is not expected to occur instantaneously, but requires some time for their insertion into the membrane.…”
Section: Are Pre-formed Oligomers More Efficient Than Toxin Monomers?mentioning
confidence: 86%
“…Instead, although oligomers were shown to cause a much greater release of calcein than trypsin-activated toxin monomers, both forms of the toxin appeared to act instantaneously, at least within the time resolution of the instrument, upon addition of the toxin to the vesicle suspension Rausell et al, 2004a). This result is very surprising considering that although calcein release can be very rapid, it is nevertheless expected to take place at a measurable rate (Schwarz and Robert, 1990) as was reported for the Escherichia coli colicin E1 (Kayalar and Düzgüneçs, 1986) and hemolysin (Menestrina, 1988), the Clostridium tetani tetanus toxin (Menestrina et al, 1989), the Pseudomonas aeruginosa exotoxin A (Menestrina et al, 1991) and the mosquitocidal binary toxin from Bacillus sphaericus , to mention only a few examples of calcein-efflux experiments conducted with bacterial pore-forming toxins. Clearly, pore formation by Bt toxins is not expected to occur instantaneously, but requires some time for their insertion into the membrane.…”
Section: Are Pre-formed Oligomers More Efficient Than Toxin Monomers?mentioning
confidence: 86%
“…Indeed, the presence of a conformational transition, resulting in an increased exposure of hydrophobic sites on the surface of CryIC, is clearly indicated by the bis-ANS binding experiments. The behavior of CryIC under conditions of acidic pH shares certain characteristics common to a number of other bacterial toxins, such as diphtheria toxin [19], Pseudo-monas aemginosa exotoxin A [20,21], tetanus toxin 122,233 and colicins 124,251. All these proteins show a dramatic increase in the affinity for phospholipid membranes at acidic pH.…”
Section: Discussionmentioning
confidence: 96%
“…Another similarity between &endotoxin and some other membrane-active bacterial toxins is the preferential membrane interaction in the presence of acidic phospholipids [19,21,22,25]. In the case of CryIC, the effect of acidic lipids is clearly nonspecific and indicates that electrostatic interactions play a role in binding of the toxin to the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Ean der Goot, Gonzalez-Manas, Lakey, and Pattus (1991) observed that, depending on circumstances, the pH in the vicinity of the membrane might be 1-3 units lower than in the bulk solution. A decrease in pH has been linked to structural changes in many proteins, such as the Bt toxin Cry1C (Butko, Cournoyer, Pusztai-Carey, & Surewicz, 1994), P. aeruginosa exotoxin A (Menestrina, Pederzolli, Forti, & Gambale, 1991), tetanus toxin (Calappi, Masserini, Schiavo, Montecucco, & Tettamanti, 1992), and tumor necrosis factor a (Kagan, Baldwin, Munoz, & Wisnieski, 1992). All of these proteins increase their affinity to the membrane at acidic pH (Manceva, Pusztai-Carey, & Butko, 2004).…”
Section: Antimicrobial Activity and Hemolytic Activitymentioning
confidence: 99%